LESS IS MORE: POTENTIAL OVERSCREENING FOR BREAST CANCER IN U.S. NURSING HOMES. (11th November 2018) - Mack, D; Epstein, M; Dube, C; Clark, R; Lapane, K
Abstract: US guidelines regarding when to stop routine breast cancer surveillance with mammography screening remain unclear. Consequently, it is unclear if a long-term care population receives this service. The objectives of this cross-sectional study were to estimate the extent to which mammography screening occurs among US long-term care nursing home residents, and to identify resident- and regional- level factors associated with its use including geographic variation. The study sample included women aged ≥65 years residing in nursing homes for at least one year, with an annual Minimum Data Set (MDS) 3.0 assessment, continuous Medicare Part B enrollment, and no strong clinical indication for mammography screening (n=389, 821). Using 2011 Physician/Supplier Part B claims, we estimated the prevalence of mammography screening stratified by guideline age classification (65–74, ≥75 years). Associations between mammography screening and independent predictor variables were estimated by crude and adjusted prevalence ratios from robust Poisson regression models accounting for the clustering of residents within nursing homes. Mammography screening among long-term nursing home residents occurs, despite being an older population that is mostly disabled (77.9%) and cognitively impaired (76.3%) with an average life expectancy <5 years. In one year, mammography screening prevalence was 7.1% among those aged 65–74 years (95% Confidence Interval (CI): 6.8% - 7.3%) and 1.7% among those >75 years (95% CI: 1.7% - 1.8%), with geographic variation observed. Older age, cognitive impairment, frailty, and hospice were inversely associated with screening. Thoughtful consideration about individual screening recommendations and the implementation of more specific guidelines is warranted to prevent overscreening.